Dinâmica populacional de artrópodos em plantio inicial de Eucalyptus grandis (w. Hill) sob diferentes alternativas de controle químico de plantas daninhas - Garlet, Juliana (2013)
The objective of this study was to investigate the effect of alternative chemical control of weeds in the arthropod fauna in Eucalyptus grandis (W. Hill). The study was conducted in an area belonging to Fepagro Forests in Santa Maria, RS, with planting of E. grandis, being composed of the following treatments: T1 - Chemical control of weeds with glyphosate in total area (planting rows and lines), T2 - Total Chemical control of weeds in the crop row (50 cm), T3 = Chemical control of plants grasses and weeds in the row spacing of planting, T4 - chemical control of broadleaved weeds in row spacing and planting, T5 - full control of weeds in strips with a width of 1.0 m beside the row, leaving 1. 0 m interrow unchecked, T6 - Treatment (control). Results showed that the herbicides glyphosate, bentazon and setoxidin and in doses not have a direct influence on the mega, macro and mesofauna of the soil, and environmental variables have influence on the temporal distribution of soil fauna, with significant interaction between treatment and the collection periods for most groups edaphic collected. Observed that the treatments with vegetation strips of weeds with fewer plants attacked by insects pests, and greater diversity of soil organisms collected, in addition to providing significant ground cover, and showing good initial development when compared to treatment with control of weeds. Accordingly, the adoption of tracks chemical control of weeds with herbicides for the control of weeds in Eucalyptus, constitutes a viable alternative to be used in programs for Integrated Pest Management, by increasing plant diversity and arthropod, ecosystems grown.